IMPLEMENTASI KEBIJAKAN PROGRAM BANTUAN BESISWA BIDIKMISI DI POLITEKNIK NEGERI MANADO - Johannes Kristoffel Santie; Agus Wahono (MAP (Jurnal Manajemen dan Administrasi Publik), 2018)
This study aims to discuss the implementation of Bidikmisi scholarship assistance policy in Manado State Polytechnic. Theories and definitions relating to public policy initiate the review process undertaken by the author after looking into issues related to the implementation process of the Bidikmisi scholarship assistance. The research was conducted in Manado State Polytechnic by considering the implementation process of Bidikmisi scholarship aid from 2010 until 2016. The research data was obtained through observation, interview, and literature study. The respondents are Director, Vice Director of Academic Affairs, Deputy Director of Student Affairs and some administrative staffs as well as some Bidikmisi scholarship students. The data is then analyzed and described to know how the implementation process of Bidikmisi scholarship assistance policy takes place in Manado State Polytechnic. The result of the research shows that the implementation of Bidikmisi scholarship program policy in Manado State Polytechnic from 2010 until now is conducted based on the program guideline Keywords: scholarship, implementation, public policy